The Correlation Between Academic Self-Efficacy and Students Anxiety in Facing Final Exams at SMP Negeri 2 Padang - Jefri Sarhan; Mursyid Ridha (Universitas Negeri Padang, 2020)
Students anxiety is a state of the student's condation which characterized byphysical and psychological tension that will affect academic success and concentration. furthermore, self-efficaci is also one of the influencing factors. This study aims to see the description of academicself-efficacy and student anxiety when facing final exam at SMP Negeri 2 Padang. This research is descriptive correlational research. With a sample size of 127 students who were selected using a proportional random sampling technique. The data was collectingusing academic self-efficacy questionnaires and student anxiety questionnaires facing final exams with a Likert scale model. The results showed (1) the academic self-efficacy of students, in general, was in the high category as many as 71 people with 55.91%, (2) the anxiety of students facing final exams was mostly in the moderate category as many as 69 people with a score of 54.33%, (3) there is a significant negative correlation between academic self-efficacy and students' anxiety facing final semester exams at SMP Negeri 2 Padang of -0.609 with a significance value of 0.00. These findings can be used as a reference for counseling teachers in making programs to provide BK services to students.